Evaluation and comparison of the collection of selected PAASCU level II accredited high school libraries in Quezon City through collection mapping and its implications in collection development - Macrohon, Denise Marie O. (2015)
Nowadays, school libraries and media centers are becoming more relevant. Thus, it is important to maintain a quality collection to support the school's mission, vision, and goals. School librarians must find ways to evaluate the collection to ensure that the best materials may be delivered effectively to the users.